2009
DOI: 10.1021/tx900326k
|View full text |Cite
|
Sign up to set email alerts
|

Cheminformatics Analysis of Assertions Mined from Literature That Describe Drug-Induced Liver Injury in Different Species

Abstract: Drug Induced Liver Injury (DILI) is one of the main causes of drug attrition. The ability to predict the liver effects of drug candidates from their chemical structure is critical to help guiding experimental drug discovery projects towards safer medicines. In this study, we have compiled a dataset of 951 compounds reported to produce a wide range of effects in the liver in different species, comprising humans, rodents, and non-rodents. The liver effects for this dataset were obtained as assertional meta-data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 27 publications
2
119
0
Order By: Relevance
“…There have been efforts recently to use computational models to predict DILI or idiosyncratic hepatotoxicity. We are aware of at least three studies that tackled predicting DILI dmd.aspetjournals.org using either linear discriminant analysis, artificial neural networks, and machine learning algorithms (OneR) (Cruz-Monteagudo et al, 2008), support vector machine (Fourches et al, 2010a), or structural alerts (Greene et al, 2010). A major limitation of these previous global models for DILI (and for many computational toxicology models) is their use of very small test sets in all cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been efforts recently to use computational models to predict DILI or idiosyncratic hepatotoxicity. We are aware of at least three studies that tackled predicting DILI dmd.aspetjournals.org using either linear discriminant analysis, artificial neural networks, and machine learning algorithms (OneR) (Cruz-Monteagudo et al, 2008), support vector machine (Fourches et al, 2010a), or structural alerts (Greene et al, 2010). A major limitation of these previous global models for DILI (and for many computational toxicology models) is their use of very small test sets in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Assembling high-quality datasets for the purpose of computational analysis can be very challenging. Commonly public data sources are used as trusted resources of information and without further validation, and, as has been demonstrated or suggested in a number of previous studies, this is not appropriate (Williams et al, 2009;Fourches et al, 2010a and references therein). The set of validated chemical structures used as the training and test data were assembled from the ChemSpider database (http:// www.chemspider.com).…”
Section: Methodsmentioning
confidence: 99%
“…Our recent studies provide specific examples demonstrating that the use of cheminformatics approaches helped spotting gaps or errors in biological annotations of toxic compounds. [20,31] …”
Section: The Importance Of Chemical Data Curation In Qsar Modelingmentioning
confidence: 99%
“…[93] Fourches et al evaluated animal human data for 1061 compounds known to cause hepatotoxicity in humans and found that the concordance or sensitivity among species was around 39-44%. [94] The positive and negative predictive values could not be calculated from the article but would be well below 0.39. Smith and Caldwell studied twenty-three chemicals and discovered that only four were metabolized the same in humans and rats.…”
Section: Prediction In Sciencementioning
confidence: 98%